Analisis Efektivitas Marketing Media Sosial Instagram Terhadap Keputusan Pelanggan Dezato Brownies - Moh. Fatur Gifahri; Harifuddin Thahir; Syamsul Bahri Dg. Parani; Suryadi Samudra (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
The purpose of this study was to determine the effectiveness of social media marketing instagram in the dimensions of content creation, content sharing, connecting, and community building on customer decisions Dezato BrowniesThe type of research used is descriptive qualitative. Sedarmayanti and Hidayat (2011: 33) define qualitative descriptive research as a method in finding facts about the status of a group of people, an object, a condition, an event in the present with the right interpretation. This is in line with the test results which show that social media marketing with the variables Content Creation, Content sharing, Connecting, Communitiy Building is very effective on Dezato Brownies' customer decisions. It can be concluded that social media marketing effectively increases customer awareness, interaction, and purchasing decisions, making a positive contribution to business growth. Keep in mind that customer purchasing decisions are influenced by complex factors beyond the variables studied, confirming the complexity of market dynamics and consumer behavior.